A recyclable protein resource derived from cauliflower by-products: Potential biological activities of protein hydrolysates. (15th April 2017) - Xu, Yang; Li, Yuting; Bao, Tao; Zheng, Xiaodong; Chen, Wei; Wang, Jianxu
Highlights: Cauliflower by-product is an economic protein resource. Ultrasonic-assisted extraction of leaf protein was investigated. 12.066 g of leaf protein was obtained from 1 kg of cauliflower by-product. The protein hydrolysate showed angiotensin I-converting enzyme inhibitory activity. The protein hydrolysate may have glucose-lowering effect. Abstract: Cauliflower by-products (CBP) are rich in leaf protein. Every year tons of CBP will lead to environmental pollution. Therefore, this study was conducted to extract leaf protein from CBP and investigate its biological activities. Our results showed that the optimal extraction parameters were: a liquid to solid ratio of 4 mL/g, a pH of 11, an ultrasonic extraction lasting 15 min, and at an applied power of 175 W. Under these optimized conditions, 12.066 g of soluble leaf protein (SLP) was obtained from 1000 g of CBP and its extraction yield was 53.07%. The obtained SLP was further hydrolysed by Alcalase and the SLP hydrolysate (SLPH) showed a potent angiotensin I-converting enzyme (ACE) inhibitory activity with an IC50 value of 138.545 μg/mL in vitro . In addition, SLPH promoted the glucose consumption and enhanced the glycogen content in HepG2 cells. Overall, our results suggested that CBP may be recycled for designing future functional foods.